1980
DOI: 10.1139/o80-164
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of sulfogalactosylalkylacylglycerol in a plasma membrane fraction from adult rat testis

Abstract: Adult rat testis homogenates were fractionated by differential centrifugation followed by two discontinuous gradient centrifugation steps under identical conditions except for the absence of digitonin in the first gradient and the presence of 0.03% digitonin in the second gradient. The first gradient centrifugation yielded a membrane fraction enriched 28.8-fold in 5'-nucleotidase, 21.5-fold in UDP-Gal:GlcNAc galactosyltransferase and 18.6-fold in UDP-GlcNAc:alpha-D-mannoside N-acetylglucosaminyltransferase. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…6). Other studies carried out in this laboratory have shown that SGG is greatly enriched in a plasma membrane fraction prepared from mature rat testis homogenates (27). Attempts to cleave SGG on the spermatozoan cell surface with arylsulfatase A were unsuccessful although SGG proved an effective substrate in vitro .'…”
Section: Discussionmentioning
confidence: 97%
“…6). Other studies carried out in this laboratory have shown that SGG is greatly enriched in a plasma membrane fraction prepared from mature rat testis homogenates (27). Attempts to cleave SGG on the spermatozoan cell surface with arylsulfatase A were unsuccessful although SGG proved an effective substrate in vitro .'…”
Section: Discussionmentioning
confidence: 97%
“…Other studies (7, 18) have indicated that the synthesis of SGG is limited to an early stage of spermatogenesis, probably the primary spennatocytes. SGG has been shown to be located primarily in the plasma membrane fraction of spermatogenic cells (19,20). Taken together, these various findings suggest that, once SGG is synthesized early in spermatogenesis, it resides primarily in the plasma membrane in a condition of almost complete metabolic stability during all of the complex morphogenetic events (21) that accompany the conversion of a relatively undifferentiated spematocyte to a mature spermatozoon.…”
Section: Discussionmentioning
confidence: 93%
“…We have also shown by immulnoflusrescence that SGG is expressed on the cell surface of spermatocytes and spermatids (12). Other studies have fsund that SGG is greatly enriched in the plasma membrane of testicular cells (22,23 ) .…”
Section: ) and Several Intestinal Sulfslipidsmentioning
confidence: 93%